Congenital Strangulated and Gangrenous Epigastric Hernia in A Male Neonate - Ahmed, Minhaj (Iranian Journal of Pediatric Surgery, 2024)
Epigastric hernia (EH) is hernia of linea alba above umbilicus. An uncommon surgical condition & account for 3-5% of the population with male predominance. EH have high risk of incarceration & strangulation because of tight fascial defect of linea alba. Congenital epigastric hernia refers to herniation of intra- abdominal organs from the xiphoid process to the umbilicus due to failure of proper attachment of the rectus muscle during development and a hernia is called strangulated when its blood supply of its contents is compromised. A congenital strangulated and gangrenous epigastric hernia is very rare & is associated with significant morbidity and mortality.